Dealing with dreams: Applied study on students at the university level - Mohamad, Omar Abu Al-Majd; Ibraheem, Abdullah Omar Al-Haj (Research Journal in Advanced Humanities, 2024)
Seeking the interpretation of dreams vary from person to person. Some people may feel that it is urgent to get their interoperation. Other people may ignore their dreams and never seek their interpretation. Therefore, the present study aims to explore the Saudi university students’ response toward their dreams while responding to a survey addressing their responses to the dreams they saw while they were sleeping. Among the most important findings of the study is that the majority of the students have shown “neutral” response toward their dreams. It has been also noticed that many students do not care whether their dreams are going to occur or not.  It seems from the analysis of the students’ response that the Saudi university students do not focus their attention too much on interpreting the dreams because they are engaged with their academic studies as university student. However, according to their answers, they pay attention to some of their dreams, and seek to interpret them and know their meanings. They did not rely on a scientific method for interpreting their dreams.